DESCRIPTION OF THE SPECIESBRADYBAENA PLECTOTROPIS LIVING IN THE VICINITY OF THE NARYN RIVER - Feruza Pardabaevna, Gaibnazarova; Khilola, Khakberdiyeva (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study aimed to investigate the terrestrial malacofauna in the Naryn River region, with a specific focus on Bradybaena plectotropis in Grigorievskoe Gorge, Kyrgyzstan, to enhance understanding of its ecological roles and biological features. Methods: Field surveys and anatomical analyses were conducted in August 2024, covering diverse biotopes across Grigorievskoe Gorge and Boom Gorge. Forty specimens were collected, documented, and examined for morphological and reproductive characteristics to determine ecological preferences and habitat distribution. Results: The study identified Bradybaena plectotropis as a dominant species in the region, demonstrating significant morphological adaptations and ecological versatility. Its roles in soil formation, organic matter decomposition, and trophic chains underscore its ecological importance. Additionally, its presence across varied biotopes highlights its adaptability and widespread distribution. Novelty: This research provides the first comprehensive faunistic and anatomical study of Bradybaena plectotropis in the Naryn River region, offering valuable insights into its taxonomy, ecological roles, and conservation relevance in Kyrgyzstan's mountainous ecosystem.